Recurrent Deep Neural Networks for Real-Time Sleep Stage Classification From Single Channel EEG - Bresch, Erik; Großekathöfer, Ulf; Garcia-Molina, Gary (Frontiers in Computational Neuroscience, 2018)
Objective: We investigate the design of deep recurrent neural networks for detecting sleep stages from single channel EEG signals recorded at home by non-expert users. We report the effect of data set size, architecture choices, regularization and personalization on the classification performance. Methods: We evaluated 58 different architectures and training configurations using 3-fold cross validation. Results: A network consisting of convolutional (CONV) layers and long short term memory (LSTM) layers can achieve an agreement with a human annotator of Cohen’s Kappa of ~0.73 using a training data set of 19 subjects. Regularization and personalization do not lead to a performance gain. Conclusion: The optimal neural network architecture achieves a performance that is very close to the previously reported human inter-expert agreement of Kappa 0.75. Significance: We give the first detailed account of CONV/LSTM network design process for EEG sleep staging in single channel home care setting.